2008
DOI: 10.1088/1741-2560/6/1/016001
|View full text |Cite
|
Sign up to set email alerts
|

Creation of highly aligned electrospun poly-L-lactic acid fibers for nerve regeneration applications

Abstract: Aligned, electrospun polymer fibers have shown considerable promise in directing regenerating axons in vitro and in vivo. However, in several studies, final electrospinning parameters are presented for producing aligned fiber scaffolds, and alignment where minimal fiber crossing occurs is not achieved. Highly aligned species are necessary for neural tissue engineering applications to ensure that axonal extension occurs through a regenerating environment efficiently. Axonal outgrowth on fibers that deviate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
249
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(265 citation statements)
references
References 46 publications
7
249
0
Order By: Relevance
“…PLLA filaments have been proposed as a promising tool for axon growth and guidance [67]. A special feature of our conduit is a triple-layer porous structure, which results in a more specific pore architecture than comparable solutions [68].…”
Section: Discussionmentioning
confidence: 99%
“…PLLA filaments have been proposed as a promising tool for axon growth and guidance [67]. A special feature of our conduit is a triple-layer porous structure, which results in a more specific pore architecture than comparable solutions [68].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that aligned fibres can influence the orientation of the cell type seeded upon them (Bashur et al, 2006;Bian and Bursac, 2009;Choi et al, 2008;Courtney et al, 2006;Huang et al, 2006;Lehnert et al, 2004;Riboldi et al, 2005;Wang et al, 2009). Other studies have incorporated natural biologic materials e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment of polymer nanofibres can be controlled by selecting the relevant collector plate: stationary or very slow rotation of the collector plate can be used to manufacture randomly oriented fibres, whereas a highspeed rotating mandrel can be used to create aligned fibres (Bian and Bursac, 2009;Blackwood et al, 2008;Courtney et al, 2006;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the fiber to collect along the direction of rotation. Small diameter tubes can also be fabricated by this method and have been used in vascular repair studies [16]. A high rotation speed produces increased fiber alignment as compared to lower rotation speed, but may cause fiber discontinuity [15,17].…”
Section: Overview Of the Electrospinning Processmentioning
confidence: 99%